EXPLORING STUDENT SATISFACTION AND ATTITUDES TOWARD CHATGPT IN HIGHER EDUCATION: INSIGHTS FROM A TWO-YEAR CROSS-DISCIPLINARY STUDY - Aleksander Aristovnik; Dejan Ravšelj (PEOPLE: International Journal of Social Sciences, 2025)
The launch of ChatGPT by OpenAI in November 2022 marked a major milestone in integrating artificial intelligence into higher education. Its advanced natural language processing capabilities and user-friendly design have rapidly transformed study practices worldwide, sparking both enthusiasm and critical debate among educators. This study explores student satisfaction and attitudes toward ChatGPT over two academic years (2023–2024 and 2024–2025), drawing on data from a large-scale global survey involving 23,218 and 22,963 students from more than 120 countries. Employing descriptive statistics and independent-sample t-tests, the analysis reveals a steady increase in the adoption and integration of ChatGPT into everyday academic routines. Students most frequently used the tool for brainstorming, summarizing lengthy texts, research assistance, and study support. Satisfaction also improved over time, with more than two-thirds of respondents reporting that using ChatGPT was interesting and helpful, and over half perceiving it as more useful than traditional search engines. However, despite these positive perceptions, many students still preferred human interaction, citing the AI’s lack of social presence and its limitations in addressing complex, subjective academic content. Importantly, the study identifies notable differences across academic disciplines: students in applied sciences and technology fields expressed the highest satisfaction, valuing ChatGPT’s technical assistance and clarity of information, while those in the social sciences and humanities demonstrated a stronger preference for guidance from human educators. These findings underscore ChatGPT’s rapidly growing role in higher education and highlight the need for institutions to adapt policies and teaching practices to support responsible and effective use. The insights provided offer valuable guidance for educators and policymakers seeking to harness the benefits of generative AI while addressing students’ diverse expectations and concerns.